2018
DOI: 10.1021/acsami.7b17394
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-Derived Silicon Oxycarbide Ceramics as Promising Next-Generation Sustainable Thermoelectrics

Abstract: We demonstrate the potential of polymer-derived ceramics (PDC) as next-generation sustainable thermoelectrics. Thermoelectric behavior of polymer-derived silicon oxycarbide (SiOC) ceramics (containing hexagonal boron nitride (h-BN) as filler) was studied as a function of measurement temperature. SiOC, sintered at 1300 °C exhibited invariant low thermal conductivity (∼1.5 W/(m·K)) over 30-600 °C, coupled with a small increase in both Seebeck coefficient and electrical conductivity, with increase in measurement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…PDCs are well-known to exhibit a wide range of conductivity (σ) from the insulating to the conducting regime depending on the material composition, free carbon content, and processing method. [4,61] σ of PDCs pyrolyzed at temperatures below 1300 °C is poor, usually being below 10 −5 S cm −1 at room temperature. [14,20,21,[62][63][64][65][66][67][68][69][70][71][72][73][74] Poor σ limits the functional applications of PDCs.…”
Section: Abnormal Electrical Behaviors In Pdc-sicnmentioning
confidence: 99%
“…PDCs are well-known to exhibit a wide range of conductivity (σ) from the insulating to the conducting regime depending on the material composition, free carbon content, and processing method. [4,61] σ of PDCs pyrolyzed at temperatures below 1300 °C is poor, usually being below 10 −5 S cm −1 at room temperature. [14,20,21,[62][63][64][65][66][67][68][69][70][71][72][73][74] Poor σ limits the functional applications of PDCs.…”
Section: Abnormal Electrical Behaviors In Pdc-sicnmentioning
confidence: 99%
“…The integration of polymer-derived ceramics (PDCs) in anode materials for lithium-ion batteries is an attractive prospect that has been the focus of numerous studies since the early work on lithiation of PDCs, reported in 1994 . PDCs, which are generally carbide and oxycarbide materials formed by the pyrolysis of silicon-based preceramic polymers, are of growing interest toward diverse applications including electrochemical energy storage, microbial bioelectrochemical systems, microelectromechanical systems, electromagnetic shielding, and thermoelectrics . The development of PDCs is motivated by their remarkable chemical stability and the versatile routes with which they can be processed. , Coupled with tunable properties of electrical conductivity, permittivity, and thermal conductivity, PDCs offer utilitarian pathways toward effective energy materials. ,, …”
Section: Introductionmentioning
confidence: 99%
“…In this work, polymer-derived ceramics (PDCs) technology was used to develop SiOC ceramic materials through a pure liquid system. Combined with 3D printing technology, the limitations of hot-pressing and other formulation methods on material [42] SiOC 1450-1650 hotpressed -1.30-1.80 [43] SiOC 1100-1200 PECS 2.22 0.82 [44] SiOC 1000 3D printing shapes have been overcome. After optimizing the resin formulation, which has a better fluidity when there was no solvent and it was suitable for 3D printing.…”
Section: Discussionmentioning
confidence: 99%